Financial Crisis and Contagion Effects to Indian Stock Market: 'DCC–GARCH' Analysis. (February 2015) - Chittedi, Krishna Reddy
The study applies the dynamic conditional correlation (DCC) bivariate generalized autoregressive conditional heteroskedasticity (GARCH) model of Engle (2002 ) in order to capture the contagion effects during global financial crisis. We used daily stock returns for the period January 2002–December 2011 to study the contagion effects from the United States (US) to India. We have considered January 2002–December 2007 as the pre-crisis period and January 2008–December 2011 as crisis period. Empirical findings show that there has been a significant increase in the mean of correlation coefficient between the markets in the crisis periods compared to the pre-crisis period. This proves the existence of contagion between the US and Indian markets. However, this enhanced correlation does not lead to the removal of international diversification benefits since emerging markets still outperform in the long run due to reduced volatility. Finally, it should be noted that the presence of investment barriers and the importance of country-specific risks curtail foreign participation, even though it has grown considerably in a diminishing manner over time.